1990
DOI: 10.2466/pms.1990.71.3.848
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Athletic Injuries by Athletes, Coaches, and Medical Professionals

Abstract: 35 athletes, their coaches, and medical professionals independently assessed the disruption, seriousness, and short-term effects of the athletes' athletic injuries. Athletes underestimated the disruption and short-term effects of the injury when compared to medical professionals. 25 lower level athletes and those with no previous serious athletic injury overestimated the short-term effects of their injuries. Coaches overestimated the disrupting effects of the injury for 10 higher level athletes and 25 athletes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…A paucity of literature exists examining athlete awareness about youth sports injuries, and none exists specific to youth climbing. Unspecific to climbing, previous literature in adults has suggested that elite athletes significantly underestimated the disruptive effects of their injury [19]. Furthermore, one study [20] found a dramatic underreporting of concussions in high school athletes, an often mainstreamed topic in sports medicine, due to lack of knowledge, failure to recognize symptoms, and failure to receive medical attention.…”
Section: Introductionmentioning
confidence: 99%
“…A paucity of literature exists examining athlete awareness about youth sports injuries, and none exists specific to youth climbing. Unspecific to climbing, previous literature in adults has suggested that elite athletes significantly underestimated the disruptive effects of their injury [19]. Furthermore, one study [20] found a dramatic underreporting of concussions in high school athletes, an often mainstreamed topic in sports medicine, due to lack of knowledge, failure to recognize symptoms, and failure to receive medical attention.…”
Section: Introductionmentioning
confidence: 99%